2014
DOI: 10.1039/c4sm00975d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of self-propelled particles under strong confinement

Abstract: We develop a statistical theory for the dynamics of non-aligning, non-interacting self-propelled particles confined in a convex box in two dimensions. We find that when the size of the box is small compared to the persistence length of a particle's trajectory (strong confinement), the steady-state density is zero in the bulk and proportional to the local curvature on the boundary. Conversely, the theory may be used to construct the box shape that yields any desired density distribution on the boundary. When th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
264
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(292 citation statements)
references
References 71 publications
25
264
1
Order By: Relevance
“…Similarly, a wedge-shaped particle will experience a force towards the point of the wedge from the overlapping of the concentration boundary layers on the inside corners. This reasoning can be continued for bodies composed of straight segments joined at angles (Fily, Baskaran & Hagan 2014). The precise magnitude of the force, of course, requires a solution of (2.3)-(2.4) for the given body geometry as done in figure 3, but the fact that there should be a force can be simply reasoned.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a wedge-shaped particle will experience a force towards the point of the wedge from the overlapping of the concentration boundary layers on the inside corners. This reasoning can be continued for bodies composed of straight segments joined at angles (Fily, Baskaran & Hagan 2014). The precise magnitude of the force, of course, requires a solution of (2.3)-(2.4) for the given body geometry as done in figure 3, but the fact that there should be a force can be simply reasoned.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hydrodynamics in confinement has been studied for biological swimmers, such as bacteria and sperm, showing accumulation at the walls (30)(31)(32) and upstream swimming along surfaces (33) or in a spiral vortex (34)(35)(36). Attraction to walls has also been reported in the absence of hydrodynamics for disks (37,38), spheres (39), and dumbbell swimmers (40). But, whereas these examples study the behavior under the influence of hard boundaries, biological swimmers typically interact with soft boundaries, such as membranes and biofilms.…”
mentioning
confidence: 99%
“…when the length of the rods is sufficiently large such that the particles can diffuse over their surface before sliding off) Fily et. al [29], have shown that for large self-propelling forces the typical time t 1 a particle remains in contact with a rod scales…”
mentioning
confidence: 99%